2012
DOI: 10.1097/meg.0b013e328354834f
|View full text |Cite
|
Sign up to set email alerts
|

Higher rates of chronic hepatitis B infection and low vaccination-induced protection rates among parturients escaping HBsAg prenatal testing in Greece

Abstract: Higher HBV disease burden and low vaccination-induced protection are characteristic in pregnant women nonadherent to HBsAg prenatal testing. More intense surveillance and implementation of immunization programs should be applied in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…In a study by Malamitsi-Puchner et al, published in 1996, HbsAg (+) prevalence of 13,4% was found among Albanian pregnant women [19] and Papaevangelou et al in 2006 found a prevalence of 9.8% [9]. More recent studies show a gradual decrease to 4.9-5.4% [17,18], very similar to our findings. This trend can be explained by the ever-improving hygiene conditions among Albanian families, as well as the increasing percentage of immunization in this population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a study by Malamitsi-Puchner et al, published in 1996, HbsAg (+) prevalence of 13,4% was found among Albanian pregnant women [19] and Papaevangelou et al in 2006 found a prevalence of 9.8% [9]. More recent studies show a gradual decrease to 4.9-5.4% [17,18], very similar to our findings. This trend can be explained by the ever-improving hygiene conditions among Albanian families, as well as the increasing percentage of immunization in this population.…”
Section: Discussionsupporting
confidence: 91%
“…Native Greek pregnant women showed a low seroprevalence of 0.5% (95% CI 0.2-1) in our study, similar to the most recent surveys by Elefsiniotis et al and Karatapanis et al, reporting 0.57% and 0.6% respectively [7,18]. The 1.7% seroprevalence in Greek pregnant women that Papaevangelou et al reported in the 2003 study probably highlights the constantly falling prevalence of HBV in the Greek population [9].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the European Mediterranean countries, the overall prevalence of HBV ranges between 2.5% and 3.5% [28,29]. In contrast, North Africa is overall an area of relatively high HBV endemicity.…”
Section: Discussionmentioning
confidence: 99%
“…Such variation has also been reported in other Mediterranean countries. In Italy, Greece, France and Spain, the prevalence of these viruses varies greatly from one region to another within the same country [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%